The trust-mistrust dynamic in the public governance of sport: exploring the legitimacy of performance measurement systems through end-users' perceptions - Fahlen, J. (International Journal of Sport Policy and Politics, 2017)
With increased government involvement in sport has followed a perceived need to audit the performance of sport organisations. This has created a wide range of performance measurement systems aiming at producing information to assist in managerial decisions and policymaking. Although thought of as improving organisational performance, it has also been argued that performance regimes, especially in the government/third-sector nexus, are threatening the self-determination of autonomous organisations. Thus, the purpose of this article is to add to the existing understanding of how audits and measurements affect the organisations they are supposed to monitor, not only in terms of minor and negligible side effects, but more importantly in terms of pervasive alterations of the autonomous club sport practice. To do so, data from 43 interviews with representatives from 20 sport clubs were analysed. Findings show how the performance measurement system under study leads to an alteration of sport clubs` activities to maximise performance measures; a centralisation of work associated with measurement within the club; and an undermining of trust between the voluntary and public sectors, which challenges the legitimacy of this relationship. Thus, this study shows that performance measurement systems are dependent on the legitimacy bestowed by the agents affected by it